EVERYONE IS CONSTANTLY UPDATING: SURVEILLANCE CAPITALISM IN GARY SHTEYNGART’S SUPER SAD TRUE LOVE STORY (Al-Aasar, 2026)
This article intervenes into the new architecture of surveillance capitalism with by, tracing the novel to the recent debates in the field of data extraction, algorithmic government, and digital commodification. Although studies of the novel tend to focus on dystopian futurity, techno-consumerism and neoliberal precarity, there has been limited focus on the operation of surveillance capitalism. To remedy this research gap, the article explores how the narrative constructs the normativity of pervasive monitoring, affectometreology and anticipatory datafication in an instrumentarian social design. The study takes a methodical approach of applying Zuboff's theoretical framework along with close reading and textual analysis to examine how the novel uncovers the extraction imperative as it continuously plunders intimate human experience into behavioral surplus. The analysis shows that the text is anticipating the development of prediction products, as well as behaviour markets where sentiment, enthusiasm, consumers' interpersonal relationships are made quantifiable and acted out through the process of computing optimization. Additionally, it is stated in this article that Big Other is an all-pervading digital architecture, which is conceptualized to restructure the subjectivity, autonomy and social interaction in an asymmetrical pattern of knowledge acquisition and behavioral modification. The study's focus upon technology's entanglements and the economic procedures of extraction interfere with the existing paradigms of literary research in the areas of contemporary surveillance discussion, technocriticism, and postdisciplinary literary theory. Surrounding it, the article introduces the novel as a critical intervention revealing the epistemic, political and affective impacts of surveillance capitalism in the algorithmically mediated digital era.